Diet and supplements in cancer prevention and treatment: Clinical evidences and future perspectives. (March 2018) - Vernieri, Claudio; Nichetti, Federico; Raimondi, Alessandra; Pusceddu, Sara; Platania, Marco; Berrino, Franco; de Braud, Filippo
Abstract: In recent years, calorie-restricted dietary regimens and compounds such as vitamins, curcumin, green tea extracts and omega-3 fatty acids have attracted attention for their potential anticancer effects. While definitive conclusions cannot be drawn in this field, many patients adopt complementary antitumor therapies aiming to improve efficacy or reduce toxicity of chemotherapy, with uncertain benefits and the risk of additional toxicities or antagonistic interactions with standard therapies. In this manuscript, we review the different levels of available evidence to suggest or discourage specific dietary changes or supplement use in the context of cancer prevention, reduction of tumor recurrences and survival prolongation in advanced cancers. Preventing or treating obesity, as well as adhering to healthy dietary patterns, should be recommended to both the general population and cancer survivors because they are convincingly associated with reduced risk of primary or second cancers and, in some cases, with reduced cancer recurrences. On the contrary, the role of specific interventions or supplements in patients with advanced malignancies is much more uncertain and actually a highly debated topic. With some exceptions, such as melatonin, the use of most complementary therapies cannot be encouraged, or should be discouraged, because of the lack of sufficient safety and efficacy data.